2011
DOI: 10.1002/ar.21421
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of LAPTM4B‐35 Promotes Malignant Transformation and Tumorigenesis in L02 Human Liver Cell Line

Abstract: Hepatocellular carcinoma (HCC) is one of the most frequent malignant neoplasms worldwide and is the second leading cause of cancer death in China. We have previously demonstrated that LAPTM4B-35, encoded by lysosomal protein transmembrane 4 beta gene, is overexpressed in over 80% of HCCs and is a novel-independent prognostic factor for metastasis, recurrence, and postoperative survival in HCC. In this study, we investigated the role of LAPTM4B-35 in malignant transformation and tumorigenesis using L02 cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
(31 reference statements)
0
25
0
Order By: Relevance
“…LAPTM4B was originally identified in hepatocellular carcinoma patients as an abnormally overexpressed protein and was later found to be upregulated in many other human cancers including breast, lung, ovarian, and colon cancers (Kasper et al, 2005). Ectopic expression of LAPTM4B transforms normal cells and promotes proliferation, migration and invasion of cancer cells (Li et al, 2011a; Yang et al, 2010). LAPTM4B is proposed to promote cancer cell proliferation by upregulating PI3K/ATK signaling (Li et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…LAPTM4B was originally identified in hepatocellular carcinoma patients as an abnormally overexpressed protein and was later found to be upregulated in many other human cancers including breast, lung, ovarian, and colon cancers (Kasper et al, 2005). Ectopic expression of LAPTM4B transforms normal cells and promotes proliferation, migration and invasion of cancer cells (Li et al, 2011a; Yang et al, 2010). LAPTM4B is proposed to promote cancer cell proliferation by upregulating PI3K/ATK signaling (Li et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a previous study revealed that tissues with elevated expression of LAPTM4B had significantly more new capillary blood vessels than tissues with reduced expression in a mouse xenograft model of liver cancer, indicating that LAPTM4B over-expression might be significantly associated with increased angiogenic activity [16]. Recent studies have also shown that silencing LAPTM4B remarkably reduces the expression of VEGF in HeLa cells [17] and that increased LAPTM4B-35 combined with positive VEGF expression might serve as a new biological marker to predict outcomes in cervical carcinoma [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also shown that silencing LAPTM4B remarkably reduces the expression of VEGF in HeLa cells [17] and that increased LAPTM4B-35 combined with positive VEGF expression might serve as a new biological marker to predict outcomes in cervical carcinoma [18]. In addition, it has been proven that the upregulation of LAPTM4B-35 promotes the activation of AKT and Bad, which would maintain cell survival [16]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the overexpression of LAPTM4B-35 leads to the accumulation of a number of oncoproteins and downregulation of a number of tumor suppressing proteins. Conversely, knockdown of endogenous LAPTM4B-35 via RNAi results in remarkable inhibition of xenograft growth and metastasis of human HCC in nude mice [5,7]. Meanwhile, the RNAi knockdown of LAPTN4B-35 can reverse the cellular and molecular malignant phenotypes noted above [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HCC cells with a high expression of LAPTM4B-35 show a strong tendency to motivate drug resistance [6]. The over-expression of this gene promotes tumorigenesis, faster growth, and metastasis of human HCC xenografts in nude mice [5,7] and leads to antiapoptosis, deregulation of proliferation, enhancement of migration and invasion, and multidrug resistance [5]. In addition, the overexpression of LAPTM4B-35 leads to the accumulation of a number of oncoproteins and downregulation of a number of tumor suppressing proteins.…”
Section: Introductionmentioning
confidence: 99%